Principles of statistics for engineers and scientists - Navidi, William (McGraw-Hill, 2010)
Principles of Statistics for Engineers and Scientists" offers the same crystal clear presentation of applied statistics as Bill Navidi's "Statistics for Engineers and Scientists" text, in a manner especially designed for the needs of a one-semester course that is focused on applications. By presenting ideas in the context of real-world data sets and with plentiful examples of computer output, the book is great for motivating students to understand the importance of statistics in their careers and their lives. The text features a unique approach highlighted by an engaging writing style that explains difficult concepts clearly and the use of contemporary real world data sets to help motivate students and show direct connections to industry and research. While focusing on practical applications of statistics, the text makes extensive use of examples to motivate fundamental concepts and to develop intuition